La comunicación para el cambio social y el proceso de empoderamiento en una comunidad virtual: el caso del grupo de Facebook Ni Una Menos: Movilización Nacional Ya - Soto Canales, Valeria (2020)
The purpose of this article is to analyze the power of communicative interaction in virtual communities, in the case of the virtual community of Facebook Ni Una Menos: Movilización Nacional Ya, from the paradigm of communication for social change. In order to achieve this objective, a qualitative methodology was applied, which consisted of field work composed of in-depth interviews with 15 members of the Facebook group, as well as the analysis of virtual contents. As a result of the analysis, it was possible to observe how the characteristics of the group, created for activism, led to the sensitive disclosure of testimonies on the web portal, around which a virtual community of support was articulated. In conclusion, this analysis evidenced the power of virtual communicative interaction for the process of individual and collective empowerment of vulnerable communities, such as women victims of violence.